Anarchist Networks in Postwar Europe: Latency and Renovation between Protest Cycles - Romanos, Eduardo (Historia y Comunicación Social, 2018)
This article examines international anarchism after 1945 by focusing on two networks particularly active in Western Europe: a network of young anarchists critical of the ineffectiveness of their respective national anarchist federations, and a network of libertarian publications which spread the work of a set of intellectuals critical of the traditional principles, tactics and goals of social anarchism. These networks of exchange and communication helped to renew anarchism in a political context that was particularly unreceptive to their demands. Analysing them will allow us to better define the postwar period as a phase of low visibility within the history of anarchism that, however, saw the elaboration of new ideological principles and strategic options. In the end, this article suggests that some of these developments appeared later in protest movements that prefigured and armed the 1968 international mobilization. The working hypothesis is that the postwar latency phase bridged the contentious 1930s with the new visibility of anarchism around 1968.
Keywords: transnational networks; critical communities; cultural change; dissent; diffusion of innovations.